Penyuluhan dan Pembuatan Produk Lilin Aromaterapi Berbasis Minyak Jelantah Di Desa Sibang Kaja - Gusti Ayu Dewi Lestari; Balqish Fathoum Medinna; Jessica Sanchez Anggraini (Unika Santu Paulus Ruteng, 2023)
Indonesia is a country with a very high level of consumption of cooking oil where the amount of used cooking oil waste, is also very high in Indonesia. In general, this waste is not utilized optimally resulting in environmental pollution. To overcome the problems associated with used cooking oil, efforts are made so that this waste does not pollute the environment. One of the uses of used cooking oil is making aromatherapy candles from used cooking oil. Aromatherapy candles are candles that are made by adding fragrances with various purposes and benefits that can be used as room fresheners and to calm down. Counseling and candle making training was attended by members of the youth posyandu in Sibang Kaja Village, Abiansemal District. Participants experienced an increase in knowledge after being given an explanation regarding the manufacture of aromatherapy candle products with an initial value of 77.2% and a final value of 91.2%. From these data it shows that the difference in the average knowledge value of the participants' pretest and posttest is 14%. The existence of this value difference indicates that there is a difference between knowledge among the community before counseling and making aromatherapy candles and after this activity is carried out.